The effect of 5‐azacytidine treatment delays and dose reductions on the prognosis of patients with myelodysplastic syndrome: how to optimize treatment results and outcomes. (30th August 2020) - Diamantopoulos, Panagiotis T.; Symeonidis, Argiris; Pappa, Vasiliki; Kotsianidis, Ioannis; Galanopoulos, Athanasios; Pontikoglou, Charalampos; Anagnostopoulos, Achilles; Vassilopoulos, George; Zikos, Panagiotis; Hatzimichael, Eleftheria; Papaioannou, Maria; Megalakaki, Aekaterini; et al.
Summary: The regimen of 5‐azacytidine for patients with myelodysplastic syndrome (MDS) has remained unchanged since its first approval. Although several modifications have since been made and delays and dose reductions are common especially during the first treatment cycles, there are minimal data on the prognostic effect of these modifications. In this study, based on data from 897 patients with MDS treated with 5‐azacytidine recorded in a national registry, the effect of treatment delays and dose reductions on response, transformation to acute myeloid leukaemia, and survival (after 5‐azacytidine initiation, OST ) were analysed. Delays during the first two cycles were noted in 150 patients (16·7%) and were found to adversely affect OST independently of the International Prognostic Scoring System score [hazard ratio (HR), 1·368; P = 0·033] or pre‐existing neutropenia (HR, 1·42; P = 0·015). In patients achieving a response, delays before response achievement were correlated with its type (complete remission, 2·8 days/cycle; partial remission, 3·3 days/cycle; haematologic improvement, 5·6 days/cycle; P = 0·041), while delays after response achievement did not have any effect on retention of response or survival. Dose reductions were found to have no prognostic impact. Based on our results, treatment delays especially during the first cycles should be avoided, even in neutropenic patients. This strict strategy may be loosened after achieving a favourable response.